Shank3-Rich2 interaction regulates AMPA receptor recycling and synaptic long-term potentiation - Raynaud, Fabrice; Janossy, Andrea; Dahl, Janine; Bertaso, Federica; Perroy, Julie; Varrault, Annie; Vidal, Michel; Worley, Paul F; Boeckers, Tobias M; Bockaert, Joël; Marin, Philippe; Fagni, Laurent; et al. (The Journal of neuroscience, 2013)
Synaptic long-term potentiation (LTP) is a key mechanism involved in learning and memory, and its alteration is associated with mental disorders. Shank3 is a major postsynaptic scaffolding protein that orchestrates dendritic spine morphogenesis, and mutations of this protein lead to mental retardation and autism spectrum disorders. In the present study we investigated the role of a new Shank3-associated protein in LTP. We identified the Rho-GAP interacting CIP4 homolog 2 (Rich2) as a new Shank3 partner by proteomic screen. Using single-cell bioluminescence resonance energy transfer microscopy, we found that Rich2-Shank3 interaction is increased in dendritic spines of mouse cultured hippocampal neurons during LTP. We further characterized Rich2 as an endosomal recycling protein that controls AMPA receptor GluA1 subunit exocytosis and spine morphology. Knock-down of Rich2 with siRNA, or disruption of the Rich2-Shank3 complex using an interfering mimetic peptide, inhibited the dendritic spine enlargement and the increase in GluA1 subunit exocytosis typical of LTP. These results identify Rich2-Shank3 as a new postsynaptic protein complex involved in synaptic plasticity.